Rancangan Plugin Multiplayer Game MOODLE Learning Management System (LMS) berbasis WebSocket pada Google Cloud Server yang Berspesifikasi Rendah - Kotama, I Nyoman Darma (Lembaga Pengembangan Kinerja Dosen, 2022)
With increasing needs for online or online learning and teaching activities, educational institutions need solutions for hosting their data online. The available options include building their own data center or renting a Virtual Private Server (VPS) service that is widely available. Considering the high setup and maintenance costs, many institutions choose VPS rental options such as Google Cloud Server. Moodle Learning Management System (LMS) is one of the most affordable and open-source online learning software solutions for low-cost servers. This paper will discuss the design and implementation of the Moodle Plugin that utilizes WebSocket technology to accommodate the interactive learning process with Multiplayer Games. The result of the study reports that the plugin can accommodate and simulate an increase of 1% in CPU per 15 connections and an increase of 2MB per 15 connections. Which concluded still an affordable solution for low-cost servers for real-time connection.